How Knowledge Management Plays an Effective Role in Organizations to Make HRM More Efficient by Using System Dynamics? - Naseem, Saneela; Shah, Sayyed Sadaqat Hussain (Journal of Asian Business Strategy, 2020)
Knowledge management has emerged as an important tool for measuring organization performance leading to organizational sustainability and profitability. The intent of this paper is to discover the significant impact of the knowledge management system on organizational effectiveness enhance by system dynamics. For this purpose, the study uses the primary data; collected through structured interviews of the human resource personnel of Lahore University of Management Sciences. Overall results exhibit non-linear exponential relation which means one unit change in knowledge management double the change in organizational effectiveness. Additionally, a positive linear trend of employee productivity unveils the fact that diverse behavior only curtails organization efficiency for an initial time interval, the knowledge creation-stage, and hence after organization efficiency increases with an increase in knowledge. This study helps to facilitate the policymaker in a better understanding of knowledge-based solutions on diverse employee behavior and organizational inefficiency. These solutions will emerge into new innovative ideas to cater to the business environment pressures, particularly in competitive advantage.